The Religious Lawyering Critique - Green, Bruce A. (Journal of law and religion, 2006)
One might think about the relationship between law practice and religion in different ways, depending on how one views either the professional norms or religious belief and observance. Some of the most recent academic literature on "religious lawyering" is premised on a highly critical view of the profession's norms and a claim that religious convictions that bear on the practice of law are incompatible with, and preferable to, aspects of the professional norms. My purpose here is to identify, and raise some questions about, both this critique and this suggestion, and to show how they are in tension with other insights of the religious lawyering literature.A conception of the relevance of religion to lawyers' work need not begin with a critical view of professional norms and professionalism. On the contrary, one might start with the premise that the legal profession's expectations for law practice are socially and morally laudable, and perceive lawyers' religious convictions as providing support for good lawyering. This was the understanding expressed by Henry A. Boardman, a Presbyterian Minister, in an 1849 oration that was surely among the earliest recorded reflections on the relevance of religion to the work of U.S. lawyers.